Early-life predictors of retirement decisions and post-retirement health - Matthew H. Iveson; Ian J. Deary (Elsevier, 2019)
It remains unclear whether retirement circumstances are associated with better or worse post-retirement health. This is partly due to confounding between measures of retirement circumstances and a tendency to account only for covariates around retirement age. The present study examined the contributions of both retirement age and retirement type, independently, to post-retirement health around age 77 years. It also examined whether these contributions remain once earlier life-course factors - social class, cognitive ability and education - were accounted for. Our sample was 742 Scottish people who took part in the Scottish Mental Survey 1947. In a path model including life-course predictors, retirement type (reason), but not age, significantly predicted post-retirement health, with ill-health retirement associated with poorer physical (β = 0.455, 95% CI [0.313, 0.597], p < 0.001) and mental health (β = 0.339, 95% CI [0.191, 0.486], p < 0.001), and redundancy retirement associated with poorer physical health only (β = 0.200, 95% CI [0.069, 0.331], p = 0.004). Of the life-course predictors, higher adult social class was associated with later retirement (β = 0.115, 95% CI [0.034, 0.196], p = 0.006) and higher childhood cognitive ability was associated with increased odds of voluntary retirement (OR = 1.054, 95% CI [1.005, 1.105], p = 0.032), but no indirect contribution to health (mediated by retirement circumstances) was significant. At the same time, higher childhood cognitive ability directly predicted better post-retirement physical health (β = -0.110, 95% CI [-0.216, -0.004], p = 0.041), independently of retirement circumstances. This study demonstrates the importance of considering retirement circumstances beyond age, and of accounting for confounding between retirement circumstances and earlier life-course factors. Keywords: Retirement age, Retirement type, Health, Childhood cognitive ability, Education